A randomized trial of prophylactic platelet transfusion after cytotoxic chemotherapy in adult acute leukaemia - Dipta, Tashmim Farhana; Rahman, Md Jalilur (Bangladesh Journal of Pathology, 2010)
Key words: Acute leukaemia, chemotherapy, prophylactic platelet transfusion, platelet count increment DOI: 10.3329/bjpath.v25i1.4124 Bangladesh J Pathol 25(1): 3-9